A review of technical solutions and simulation approaches for ship collisions with lock gates. Issue 1 (February 2015) - Ehlers, S.; Le Sourne, H.; Buldgen, L.; Ollero, J.; Robertson, C.; Rigo, P.
Abstract : Lock gates are frequently found at inland waterway locks and sea navigation locks. Entering a lock with a ship is a challenging manoeuvre, which can potentially lead to the ship colliding with the lock gate. Such collision may permanently damage the gate causing the lock operation to be disrupted and the ship transport to be delayed. Consequently, it is important to design for the possibility of a ship colliding with the lock gate to ensure its operability as well as the safety of the operation. In order to do so, a variety of recommendations and standards exist, which are however neither unified nor require the assessment of the lock under a ship collision on a mandatory basis. Therefore, this paper presents the current developments in assessment approaches for ship collisions with lock gates as well as current gate protection practices. The paper concludes with a recommendation of assessment approaches, which can be used to identify safe lock gate approach velocities in the case of existing locks or collision resistant structural layouts for new buildings of lock facilities.